Palladium/Sensory Component-Catalyzed Homocoupling Reactions of Aryl Halides - Bao, Fengyu; Liu, Zhikai; Bai, Haixin; Zhang, Haiyan; Liu, Pengfei; Zhang, Qidong; Chai, Guobi (Synlett, 2020)
A novel and efficient catalyst system was developed for homocoupling reactions of aryl halides. The catalyst system consists of Pd(OAc)2 and the peppery sensory component of tobacco leaves. This is the first time that a sensory component has been used in an organic reaction. Experiments using the catalyst system showed that the reactions proceeded smoothly under air in the absence of both an additional ligand and a reductant. Furthermore, the catalyst system can be applied to the coupling reactions of hetaryl iodides. Many functional groups (including a hydroxy group) are tolerated.
Keywords: palladium catalyst; sensory component; homocoupling; aryl halides; biaryls